2013
DOI: 10.1155/2013/321725
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training for Schizophrenia in Developing Countries: A Pilot Trial in Brazil

Abstract: Cognitive deficits in schizophrenia can massively impact functionality and quality of life, furthering the importance of cognitive training. Despite the development of the field in Europe and in the United States, no programmes have been developed and tested in developing countries. Different cultural backgrounds, budget restrictions, and other difficulties may render treatment packages created in high income countries difficult for adoption by developing nations. We performed a pilot double-blind, randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
2
0
2
Order By: Relevance
“…Third, a learning effect with RBANS cannot be fully excluded, but such an effect is likely to be modest after 6 months, and it may affect both groups equally. 28 Fourth, we did not record the use of antipsychotic medication during the follow-up period. This is likely to influence the results of RBANS because previous studies showed that cognitive function in patients with schizophrenia may be affected by antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a learning effect with RBANS cannot be fully excluded, but such an effect is likely to be modest after 6 months, and it may affect both groups equally. 28 Fourth, we did not record the use of antipsychotic medication during the follow-up period. This is likely to influence the results of RBANS because previous studies showed that cognitive function in patients with schizophrenia may be affected by antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that life skills training, including social skills, is associated with improved patient cognitive function, especially in terms of verbal ability, information processing speed, and memory. Some research has shown that these kinds of training increase problem-solving skills, the quality of conversational skills, cognitive interactions, positive symptoms, long-term visual memory, self-expression, and communication with others while reducing relapse periods [22][23][24][25]. On the other hand, reading, writing, and math training are cognitive in nature, which is related to their effect on the psychological symptoms of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…* [22][23][24][25] 3. ‫مثبت‬ ‫حافظه‬ ‫است،‬ ‫گذشته‬ ‫مثبت‬ ‫تجارب‬ ‫بر‬ ‫مداخله‬ ‫تمرکز،‬ ‫بیشترین‬ ‫که‬ ‫آنجا‬ ‫از‬ [28].…”
unclassified
“…Além da ECT, outras intervenções não farmacológicas como a terapia cognitivo-comportamental (TCC), tem se mostrado eficaz tanto na esquizofrenia de modo geral (Turner et al, 2020) como especificamente na ERC (Barretto et al, 2009). Intervenções psicossociais mais focais, como o treinamento de habilidades sociais para sintomas negativos (THS-SN) e treinamento cognitivo (TC) não parecem ter eficácia significante na redução sintomática (Kayo et al, 2020;Pontes et al, 2013), contudo, é necessário salientar que os estudos citados possuem limitações importantes como tamanho amostral pequeno, portanto seus resultados precisam ser cautelosamente interpretados.…”
Section: Esquizofrenia: Diagnóstico and Tratamentounclassified